The Effect of a TPACK-Based IPAS E-Module Integrated with Tri Nga on Elementary Students’ Scientific Critical Thinking - Elyas Djufri; Tuti Indrawati (Equator Science Journal, 2026)
This study aims to develop a TPACK-based IPAS e-module integrated with Tri Nga values and examine its effectiveness in enhancing elementary students’ critical thinking skills. A quantitative approach with a quasi-experimental two-group pretest–posttest design was employed involving 85 fifth-grade students. Data were collected using a critical thinking test and analyzed through Structural Equation Modeling (SEM) and an independent samples t-test. The findings reveal that the e-module has a positive and significant effect on students’ critical thinking, with a path coefficient of 0.76 and an R-square value of 0.58. The t-test results indicate a significant difference between the experimental and control groups (t = 5.724, p < 0.05), with a mean improvement of 13.98. These results suggest that the developed e-module is effective in improving students’ critical thinking skills. The study implies that integrating TPACK with local cultural values (Tri Nga) provides an innovative, contextual, and interactive approach to support 21st-century learning.